Partisipasi Masyarakat dalam Perencanaan Pembangunan Desa Banut Kalanaman Kecamatan Katingan Hilir Kabupaten Katingan: Community Participation in Development Planning of Banut Kalanaman Village, Katingan Hilir Subdistrict, Katingan District - Hidayat, Noor; Hidayat, Wahyu (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2017)
This study aims to explain, describe how the level of community participation in the Development Planning of Banut Kalanaman Village, Katingan Hilir Subdistrict, Katingan District. This study uses a qualitative research method, and the data source consists of primary data sources (Village Head, BPD Chairperson, Village Chief, RT Chairperson, and Community), secondary data sources (Documents relating to Community Participation in the Development Planning of Banut Kalanaman Village). Data collection techniques with observation, interviews, and documentation. The results indicate that community participation in development planning is quite good but still needs to be improved, because (1) Public awareness to attend and participate in village development planning is still weak, (2) Community activeness in expressing their opinions or opinions is very low (3) Submission information or dissemination of the direction of the village development policy is minimal does not reach all levels of the village community, (4) The city is not much involved in the planning process, the city often considers the meeting to be a mere formality.